PENGARUH IMPLEMENTASI MANAJEMEN KELAS TERHADAP PERILAKU BELAJAR MAHASISWA PADA JURUSAN MANAJEMEN PENDIDIKAN ISLAM FAKULTAS TARBIYAH DAN KEGURUAN UIN ALAUDDIN MAKASSAR - Ahmad Afiif; Ridwan Idris (Lembaga Pendidikan dan Tenaga Kependidikan (Center for Teacher Training) Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar in collaboration with Lecturer Consortium of Tarbiyah and Teacher Training, 2017)
This paper contains the results of the research which aimed to determine the ef-fect of the implementation of classroom management on students learning beha-vior at the Department of Islamic Education Management at Tarbiyah and Tea-ching Faculty of UIN Alauddin Makassar. The research approach was quantita-tive with the type of Ex Post Facto and the model of research was descriptive cor-relational study. The population of the research was all of the students of the De-partment of Islamic Education Management of Tarbiyah and Teaching Faculty. The sample consisted of 31 students. The methods that were used in the data col-lection was a questionnaire on the implementation of classroom management and a scale of learning behavior. Data analysis techniques used was simple linear reg-ression formula. The results of the research pointed-out that there was a positive correlation between the implementation of classroom management and students learning behavior. This means that the better the implementation of class mana-gement, the better the student learning behavior.